PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PUZZLE PECAHAN PADA SISWA KELAS IIC DI SDN SARIREJO - Izzah Lailatur Rohmah; Husni Wakhyudin; Harto Nuroso; Endang Tri Haryani (STKIP Subang, 2023)
This study aims to improve students' mathematics learning outcomes in class IIC and describes the steps of the problem-based learning model assisted by fractional puzzle media. The subjects of this study were class IIC students at SDN Sarirejo Semarang, academic year 2023/2024, totaling 22 students. The method used is Classroom Action Research (PTK), which lasts for two cycles. Data collection techniques in this study were observation, interviews, tests, and documentation techniques. Data analysis techniques using quantitative and qualitative data analysis The results showed that there was an increase in student learning outcomes in mathematics for each cycle. At the pre-cycle stage, learning completeness was 31.8%; cycle I obtained an average learning completeness of 81.8%; and in cycle II, there was an increase in student learning outcomes with a learning completeness of 95.5%. These results indicate that the application of the problem-based learning model assisted by fractional puzzle media can improve the mathematics learning outcomes of IIC class students. It was concluded that the application of the problem-based learning model assisted by fractional puzzle media had an impact on student learning outcomes and could improve student mathematics learning outcomes.